LITERATUR REVIEW: PENCEGAHAN CEDERA DAN REHABILITASI PADA PELARI TRAIL - Suciana Suciana; Haffafa Fayrooz Djiby; Nuryani Sidarta; Erica Kholinne (Jurnal Akta Trimedika, 2024)
Trail running is sports activity that combines two activities, namely mountain climbing and running. Trail running activities are carried out on mountains that have tracks in the form of paths, in the form of ground stones, or a mixture of sand and small rocks. Trail running was first carried out in the United States of America and continues to develop in Indonesia for example Bandung, Probolinggo, Lombok dan Banyuwangi, Which have been associated in the form of ITRA (International Trail Running Association). The majority of trail running injuries occur in the lower legs, especially the knees and ankles. The main mechanisms underlying injury and injury development include inadequate neuromotor control-balance-coordination ,running through fatigue and abnormal kinematics on a variety of terrain. Pre-Rehabilitation programs such as strengthening the kinetic chain consisting of dynamic flexibility, neuromotor strength and balance, plyometrics exercises can encourage stable and also controlled movement on trails. Educating patients about symptoms of early musculoskeletal soreness and training adjustments also proved to help prevent injuries from developing into serious overuse injuries. Regarding to the increasing number of the injury in trail runners, this article was wrote to describe the role of injury prevention and safe training to reduce the risk of injury and also early rehabilitation program for the injured runners. Study by Vincent et all that review the injury prevention, safe training and rehabilitation to return to sport was the main source in the discussion. The review result showed that educating the runners to prevent injury and how to do the safe running shown a positive impact to reduce the numbers of injury. Early rehabilitation program also shown a good impact in promoting healing in injured runners.